NECESSITY OF LANDFILLING - IMPACT ON THE ENVIRONMENT TODAY - VAĽO , Andrej; JURÍK , Norbert; LAPČÍK, Martin; LAPČÍK, Vladimír (GeoScience Engineering, 2025)
The future of waste disposal, which represents a major ecological and environmental problem in Europe and its individual countries, is still not solved in any effective way. Landfilling is directly related to the waste management programs of individual countries of the European Union, which mainly strive to mitigate the impact of waste on the environment. Improper handling of waste poses a threat to all components of the environment, therefore proper handling and subsequent processing is essential.